PENGEMBANGAN MODUL PEMBELAJARAN BAHASA ARAB BERBASIS HOTS (HIGHER ORDER THINKING SKILLS) DI FKIP UMSU - Sri Ramadhani (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study aims to develop an Arabic language learning module based on Higher Order Thinking Skills (HOTS) to improve students' higher-order thinking skills at the Faculty of Teacher Training and Education, University of Muhammadiyah North Sumatra (UMSU). The study used the Research and Development (R&D) method with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. At the analysis stage, it was found that Arabic language learning was still dominated by low-order thinking skills (LOTS) and did not provide analytical, evaluative, and creative activities as required by the OBE curriculum. The developed module was validated by material experts and learning design experts with the assessment results being in the very feasible category. A limited trial on 32 students showed a significant increase in HOTS skills, evidenced by the difference in pre-test and post-test scores, as well as an increase in the ability to analyze texts, evaluate arguments, and produce new texts in Arabic. Student responses were also very positive towards the use of the module because it was considered interesting, challenging, and helped understand Arabic texts more deeply. The results of the study indicate that the HOTS-based Arabic language learning module is effective, feasible to use, and has the potential to be widely applied in Arabic language courses at universities..